(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
The Arabic dialect preserved in the Kashkadarya region of Uzbekistan represents a unique linguistic phenomenon shaped by historical migration, prolonged language contact, and sociocultural isolation. This study aims to analyze the phonetic, morphological, lexical, and syntactic features of the Kashkadarya Arabic dialect and to determine its position within the broader spectrum of Arabic dialectology. Using qualitative methods, including field interviews and comparative linguistic analysis, the research identifies significant deviations from Classical Arabic as well as influences from Uzbek and Persian languages. The findings demonstrate that the Kashkadarya Arabic dialect retains archaic Arabic elements while simultaneously exhibiting innovations resulting from long-term contact with non-Arabic languages. This study contributes to the documentation of endangered Arabic dialects and highlights the importance of preserving linguistic diversity in Central Asia.